Relationships That Matter: Four Perspectives on AI, Work, and Organizations - Narayan, Devika; Shestakofsky, Benjamin (The Journal of applied behavioral science, 2024)
The past decade has witnessed a surge of interest in how AI will transform work and organizations, presenting scholars with the difficult task of studying emergent technologies. This article advances a relational perspective that emphasizes how firms and workers are situated in, and respond to, extra-organizational pressures and forces. We examine four sets of relationships that can frame scholarly engagement with AI: finance and technology, monopoly and competition, producers and adopters, and high-status and low-status workers. We argue that this perspective illuminates connections between levels of analysis that might otherwise seem unrelated, revealing how AI tools and practices are situated within, and contribute to, broader social, financial, and industrial dynamics.